Effect of the Homogenization Process on Titanium Oxide-Reinforced Nanocellulose Composite Membranes - Mahsuli, Taufiq; Larasati, Aisyah; Aminnudin, Aminnudin; Maulana, Jibril (Journal of Mechanical Engineering Science and Technology (JMEST), 2023)
Indonesian pineapple production can reach 200 tons per day; however, pineapples generate a significant amount of waste. Pineapple peel waste can be used to make membranes. Composite membranes containing TiO2 have dense properties, low porosity, and increase the mechanical strength of the cellulose sheet. This research uses various ultrasonic homogenizers to homogenize the distribution of nanocellulose and TiO2 (50% and 100% power with 30, 60, and 90 minutes). The casting method is used to shape the membrane. The SEM test shows that the higher the power used and the longer the sonication time, the less agglomeration of about 1.63%/ cm2 and a thickness of 16.56 µm. Identification of X-ray diffraction (XRD) results shows that sonication treatment for too long causes the peak at an angle of 25o to disappear. The analysis revealed no new peaks in the diagram pictures that were found using Fourier Transform Infrared Spectroscopy (FTIR) to analyze the functional groups, but it is known that changes occur in the O-H bonds of cellulose and C=C. The 50% sample with a power of 60 minutes had the lowest roughness value of 1.008 µm. Furthermore, as the power and time on the sample are increased, the roughness increases.